EXTRACCIÓN ÓPTIMA MULTI-RESPUESTA DE POLIFENOLES PRESENTES EN ORUJO DE UVA BAJO CONDICIONES SUBCRITICAS - León Calvo, Niltón César (2025)
Grape pomace is an agroindustrial residue with significant concentrations of polyphenols and reducing sugars, which limit its use in developing nutraceuticals. Therefore, the objective was to evaluate the effect of solvent composition (ethanol: 20–60%) and temperature (100–160°C) on polyphenols and sugar content recovery from grape pomace using a subcritical extraction process. To this end, the sample was conditioned within a pressurized liquid extraction system. Optimal extraction conditions (temperature and ethanol) were then established using a central composite design to maximize polyphenol content with minimal reducing sugars (glucose). Increased ethanol concentration (20–60%) and high temperatures improve polyphenol recovery, while the presence of ethanol reduces the extraction of reducing sugars. Conversely, temperature increases increase the presence of undesirable compounds (glucose). The optimization process maximized polyphenol recovery with minimal glucose content, with parameters set at 141.9°C with 60.3% ethanol. Therefore, using ethanol not only improves polyphenol recovery but also reduces the presence of reducing sugars. Furthermore, multiple response optimization is a technique that maximizes the yield of antioxidant compounds with minimal presence of undesirable compounds.